1999
DOI: 10.1021/la981012p
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of Palladium Clusters on γ-AlO3(111)/NiAl(110) with Transmission Electron Microscopy

Abstract: For Pd clusters on γ-Al2O3 epitaxially grown on NiAl(110) the lattice constant has been determined as a function of the cluster size by evaluating patterns induced by double diffraction involving the NiAl substrate and the cluster lattice. Similar to results reported previously for platinum and tantalum clusters on the same substrate (Surf. Sci. 1997, 391, 27; Surf. Sci. 1998, 413, 192), we observe a reduction of the distances within the lattice with decreasing cluster size. The highest observed reduction is 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 31 publications
5
39
0
Order By: Relevance
“…Further, we have shown that the origin of the initial state effect is a lattice contraction that is part of the cluster growth morphology [14,15]. In particular, the BE shift is related to the d hybridization being larger for shorter bond distances.…”
Section: P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 98%
See 2 more Smart Citations
“…Further, we have shown that the origin of the initial state effect is a lattice contraction that is part of the cluster growth morphology [14,15]. In particular, the BE shift is related to the d hybridization being larger for shorter bond distances.…”
Section: P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 98%
“…In order to study only the effect of cluster size on the BE's, we have used the bulk a 0 3:59 A. However, there is evidence from transmission electron microscopy of Pd and Pt on Al 2 O 3 that the effective a 0 for small clusters is reduced by 5%-7% [14,15]; these contractions are much larger than those found for matrix isolated Cu clusters [28]. The much larger lattice strain for supported clusters may be due to their weak interaction with the support.…”
Section: P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
See 1 more Smart Citation
“…The sizes for which properties are altered depend upon the material and the specific property. This information was extracted from many sources including lattice constants, [24] surface energy, [25] Hall-Petch breakdown, [26] superparametric temperatures, [27] hematite-maghemite phase transition, [28] TiO 2 phases, [29] CuO, [30] and oxide film thickness on Fe. [31] .…”
Section: What Makes It Nano?mentioning
confidence: 99%
“…First, the decrease in the chemisorption energy can result from the contraction of the lattice parameter of a small metal nanoparticle. Previously, it has been demonstrated experimentally 19,20 that the interatomic bond length in small metal particles decreases with decreasing particle size. It is now well established also by computational studies of various metals including Pd ͑Refs.…”
mentioning
confidence: 98%